Integration of Bioresources for Sustainable Development in Organic Farming: A Comprehensive Review - Antigolena Folina; Ioanna Kakabouki; Konstantinos Baginetas; Dimitrios Bilalis (Resources, 2025)
Organic farming relies on sustainable, eco-friendly practices that promote soil health, biodiversity, and climate resilience. Bioresources—derived from plants, animals, and microorganisms—are pivotal in replacing synthetic inputs with natural alternatives. This review presents an integrated analysis of bioresources, highlighting their classification, functionality, and role in organic systems through biofertilizers, biopesticides, organic amendments, and bioenergy. Despite their potential, challenges such as knowledge gaps, limited scalability, and technical constraints hinder their widespread adoption. The review emphasizes the ecological, economic, and social benefits of bioresource integration while identifying critical barriers and proposing strategic directions for research, policy, and practice. By addressing these gaps, bioresources can enhance nutrient cycling, pest management, and soil regeneration, offering a viable path toward sustainable agriculture. This synthesis supports the development of context-specific, circular, and resilient organic farming systems that align with global sustainability goals.